2001
DOI: 10.1016/s1074-7613(01)00109-1
|View full text |Cite
|
Sign up to set email alerts
|

IRTA1 and IRTA2, Novel Immunoglobulin Superfamily Receptors Expressed in B Cells and Involved in Chromosome 1q21 Abnormalities in B Cell Malignancy

Abstract: Abnormalities of chromosome 1q21 are common in B cell malignancies, but their target genes are largely unknown. By cloning the breakpoints of a (1;14) (q21;q32) chromosomal translocation in a myeloma cell line, we have identified two novel genes, IRTA1 and IRTA2, encoding cell surface receptors homologous to the Fc and inhibitory receptor families. Both genes are selectively expressed in mature B cells: IRTA1 in marginal zone B cells and IRTA2 in centrocytes, marginal zone B cells, and immunoblasts. As a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
187
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(194 citation statements)
references
References 47 publications
(2 reference statements)
6
187
0
1
Order By: Relevance
“…Through a combination of strategies, we and others have cloned 40 IgH translocation breakpoints (but no IgL translocation breakpoints) in MM cell lines and tumors Chesi et al, 1996Chesi et al, , 1997Chesi et al, , 1998aGabrea et al, 1999;Hatzivassiliou et al, 2001;Iida et al, 1997;Pratt et al, 2001;Richelda et al, 1997;Ronchetti et al, 1999;Shaughnessy et al, 2001;Bergsagel and Kuehl, 2001, unpublished). With the exception of a few translocation breakpoints within the JH region, most of these breakpoints were identi®ed using probes designed to detect ISRF, so that the results are signi®cantly biased in identifying translocations that occur within or relatively near an IgH switch region.…”
Section: Anatomy Of Igh Translocations In MMmentioning
confidence: 99%
“…Through a combination of strategies, we and others have cloned 40 IgH translocation breakpoints (but no IgL translocation breakpoints) in MM cell lines and tumors Chesi et al, 1996Chesi et al, , 1997Chesi et al, , 1998aGabrea et al, 1999;Hatzivassiliou et al, 2001;Iida et al, 1997;Pratt et al, 2001;Richelda et al, 1997;Ronchetti et al, 1999;Shaughnessy et al, 2001;Bergsagel and Kuehl, 2001, unpublished). With the exception of a few translocation breakpoints within the JH region, most of these breakpoints were identi®ed using probes designed to detect ISRF, so that the results are signi®cantly biased in identifying translocations that occur within or relatively near an IgH switch region.…”
Section: Anatomy Of Igh Translocations In MMmentioning
confidence: 99%
“…The FcRL genes are clustered together in the midst of the classical FcR genes, FcgRI, FcgRII, FcgRIII, and FceRI, in the 1q21-23 region of chromosome 1. This region contains 1 of the most frequent secondary chromosomal abnormalities associated with malignant phenotype in hematopoietic tumors, especially in multiple myeloma (6). FcRL5 is expressed only in the Bcell lineage, starting as early as pre-B cells, but does not attain full expression until the mature B-cell stage.…”
Section: Introductionmentioning
confidence: 99%
“…All are type I transmembrane proteins of the immunoglobulin superfamily, and display potential immunoreceptor tyrosine-based activation and/or inhibitory motifs (ITAMs or ITIMs) in their cytoplasmic domains. [3][4][5][6][7][8][9][10][11] IRTA1/FcRH4/IFGP2 was originally identified as part of an Ig-Ca1 fusion protein resulting from the translocation of chromosome 1q21 with 14q32 in a human multiple myeloma cell line. Expression of this gene was found to be localized within naïve and memory B cells of the marginal zone and epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…More recent analysis of the cytoplasmic domain of this protein has indicated that it is likely to function as a potent inhibitory receptor for regulating memory B-cell activation. 4,[6][7][8]12,13 A second homologous cDNA encoding IRTA2/FcRH5/ BXMAS1 was cloned and found to be dysregulated in Burkitt's lymphoma cell lines with 1q21 abnormalities. Transcript for this gene can be detected within naïve B cells, memory, and plasma cells of the mantle zone, interfollicular, intraepithelial, and germinal center light zones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation